Integrasi Pesantren dan Sekolah (Kajian atas Pemikiran Abdurrahman Wahid) - Herman Wicaksono (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo (previously known as IAIN Ponorogo), 2022)
Abstract Pesantren and schools should be integrated where they need to work together to improve the quality of education in Indonesia. Aside from the benefits and drawbacks of the pesantren education model, Abdurrahman Wahid, the